Strongly coupling Cu with MoP for high-efficiency electrochemical nitrate-to-ammonia conversion and zinc-nitrate battery applications - Chen Yang; Yuanyuan Chen; Zhimin He; Rong Li; Xinglong Gou (Frontiers in Chemistry, 2025)
The electrochemical nitrate reduction reaction (NITRR) offers a sustainable route for ammonia synthesis and environmental remediation but faces challenges such as sluggish kinetics and competing hydrogen evolution. This study aims to address these limitations by designing a Cu/molybdenum phosphide (MoP) heterostructure catalyst through one-pot calcination, which integrates Cu nanoparticles with MoP nanograins. Structural and electronic analyses confirm the formation of intimate Cu–MoP interfaces, where charge redistribution polarizes Cu to an electron-deficient state (Cuδ+) and enriches MoP with electrons. This configuration enhances nitrate adsorption on Cuδ+, while MoP efficiently supplies protons via accelerated water dissociation. The Cu/MoP catalyst achieves a record-high NH3 Faradaic efficiency (FE) of 98.93% and a yield rate of 30.72 mmol h−1 cm−2 at −0.5 V (vs. RHE), outperforming isolated Cu or MoP. When deployed in a Zn-nitrate battery, the composite cathode delivers a peak power density of 12.97 mW cm−2. This work provides a promising solution to the insufficient active hydrogen supply and poor NH3 conversion efficiency of Cu-based nitrate reduction catalysts.